2h+3-12h=9(-h+2)

Simple and best practice solution for 2h+3-12h=9(-h+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2h+3-12h=9(-h+2) equation:


Simplifying
2h + 3 + -12h = 9(-1h + 2)

Reorder the terms:
3 + 2h + -12h = 9(-1h + 2)

Combine like terms: 2h + -12h = -10h
3 + -10h = 9(-1h + 2)

Reorder the terms:
3 + -10h = 9(2 + -1h)
3 + -10h = (2 * 9 + -1h * 9)
3 + -10h = (18 + -9h)

Solving
3 + -10h = 18 + -9h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '9h' to each side of the equation.
3 + -10h + 9h = 18 + -9h + 9h

Combine like terms: -10h + 9h = -1h
3 + -1h = 18 + -9h + 9h

Combine like terms: -9h + 9h = 0
3 + -1h = 18 + 0
3 + -1h = 18

Add '-3' to each side of the equation.
3 + -3 + -1h = 18 + -3

Combine like terms: 3 + -3 = 0
0 + -1h = 18 + -3
-1h = 18 + -3

Combine like terms: 18 + -3 = 15
-1h = 15

Divide each side by '-1'.
h = -15

Simplifying
h = -15

See similar equations:

| 12+5=7x-4 | | 9.7s+1.56=10.9s | | -11.2b+14.16=-14.54-14.7b | | 3(x+5)=2(x+12) | | 10.1d-12.57-16.6d=-4.9d+16.39 | | 250a=11000 | | 4.95+2.95(x-3)=21.83 | | 3x+1x+2=8x-4x+2 | | 4+3x-6=3x+-12-x | | -2x-2=-8x+10 | | 4x^2-1x= | | 4(2x+4)=10x+15-2x+1l | | Sinx+cosx=-1 | | Sinx+coax=-1 | | 12k=10.6k-17.92 | | 36+3q=-5 | | 2c-4=8 | | 19-3a=13+a | | 19.8f+15.79=-13.09-16.3f | | 19-5j=-5-3j | | 14+5z=6z | | 20+4n+20=14n-20 | | -8+7w=6w | | 3(3x+2)=2(3x-6) | | 10v-9=10-4v+9 | | 2/3x-6=6-2/3x | | 6-7c=-6-10c | | 6+y=-y | | m^4-6m^2+8m-3=0 | | 3x-2=26+4x | | 7r=-10+5r | | 2a-1+7= |

Equations solver categories